2014
DOI: 10.1155/2014/824125
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Pattern during Dental Pain in Intellectually Disabled Children: A Comparative Study

Abstract: Aim. Children with developmental disabilities generally experience more pain than the normal children. Description of pain is generally difficult in children and more so in children with intellectual disabilities. The study aimed at evaluating dental pain in children with intellectual disabilities. Methods. The survey was carried out in an institution caring for intellectually disabled children to determine the oral health status and the treatment needs of the special kids. 236 children were surveyed out of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…It was reported that the oral hygiene of disabled children was poor, and they need dental treatment [9,10]. These children have problem in brushing their teeth [11].…”
Section: Dental Caries and Disabled Childrenmentioning
confidence: 99%
“…It was reported that the oral hygiene of disabled children was poor, and they need dental treatment [9,10]. These children have problem in brushing their teeth [11].…”
Section: Dental Caries and Disabled Childrenmentioning
confidence: 99%
“…Some children may exhibit autistic-like behaviour and require fixed daily routines to promote function and maintain oral health [18]. Some patients may be afraid and anxiety regarding placement of foreign objects such as toothbrushes or mouthwashes into their mouths, thereby resulting in poor oral health [32]. Patients with cognitive impairment perceive and express dental pain poorly.…”
Section: Dental Managementmentioning
confidence: 99%
“…Patients with attention deficit may be slow to comply with verbal cues or may exhibit noncooperative or defiant behavior during dental treatment (Ferreira et al 2014;Hassona et al 2017). Oral hygiene may be compromised in some patients due to fear and anxiety regarding placement of foreign objects into their mouths (Shanmugam et al 2014). Dental pain may be poorly perceived and expressed by patients with cognitive difficulties.…”
Section: Patient Managementmentioning
confidence: 99%